Kawista biscuit increased body weight of under five children - Metty Metty; Inayah Inayah (Alma Ata University Press, 2017)
ABSTRACTBackground: Underweight in under five children was a nutritional problem that is often caused by inadequate food intake. Underweight could occur at 6-59 months or should had supplemental feeding and supplementary foods. Supplementary foods have contribute energy to the nutritional adequacy of under five childrenObjective: To know the effectiveness of kawista biscuits in increasing of bodyweight under five children in Gondokusuman II Primary Health Care.Methods: Subjects were underweight with the aged of 12-59 months, as much as 19 children. The study was conducted in the working area of Gondokusuman II Primary Health Center Yogyakarta City. This study was quasi experimental with purposive technique sampling. The effectiveness of biscuit kawista a was analysed by paired t-test.Result: Based on the results of effectiveness test of biscuit kawista for 2 weeks showed significant changes in body weight children (p = 0.000) as much as 0.29 kg.Conclusion: kawista biscuit was significantly increase the weight of under five children who suffer from malnutrition. KEYWORDS: kawista biscuit (limonia acidissima), underweight, gain weight